ANALISIS PENGARUH KEPEMILIKAN PUBLIK, UKURAN DEWAN KOMISARIS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP PENGUNGKAPAN MANAJEMEN RISIKO - muhammad lukman hakim (JAF (Journal of Accounting and Finance), 2019)
This study aims to determine the effect of public ownership, board size, leverage, and firm size on Enterprise Risk Management (ERM) in companies incorporated in the LQ45 index on the Indonesia Stock Exchange in 2015 - 2017. Data collection methods in this study use data sources secondary in the form of annual reports of companies incorporated in the LQ45 index. This research uses purposive sampling with a number of samples as many as 32 companies. Based on the results of testing, public ownership, board size, leverage, and company size simultaneously have a significant effect on ERM. Partially it can be concluded that the size of the board of commissioners and leverage has a significant positive effect on ERM. Whereas public ownership and company size do not have a significant effect on ERM.